2015
DOI: 10.1039/c5nr00995b
|View full text |Cite
|
Sign up to set email alerts
|

New possibilities of accurate particle characterisation by applying direct boundary models to analytical centrifugation

Abstract: Analytical centrifugation (AC) is a powerful technique for the characterisation of nanoparticles in colloidal systems. As a direct and absolute technique it requires no calibration or measurements of standards. Moreover, it offers simple experimental design and handling, high sample throughput as well as moderate investment costs. However, the full potential of AC for nanoparticle size analysis requires the development of powerful data analysis techniques. In this study we show how the application of direct bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…AUC in combination with HDR analysis is superior to the single wavelength approach or scattering techniques. 28 Our technique takes advantage out of the direct fractionation of different size classes in the measurement cell during sedimentation, while an optimum SNR is achieved by automatically tuning the wavelengths being used for data evaluation dependent upon the particle size. The comparably high level of experimental random noise limits data quality.…”
Section: Discussionmentioning
confidence: 99%
“…AUC in combination with HDR analysis is superior to the single wavelength approach or scattering techniques. 28 Our technique takes advantage out of the direct fractionation of different size classes in the measurement cell during sedimentation, while an optimum SNR is achieved by automatically tuning the wavelengths being used for data evaluation dependent upon the particle size. The comparably high level of experimental random noise limits data quality.…”
Section: Discussionmentioning
confidence: 99%
“…At this point it should be briefly mentioned that the same holds true for analytical centrifugation (AC) which works with lower gravitational fields but extends the measurement range to larger particle sizes (Detloff T. and Lerche D., 2008;Jafarzadeh S. et al, 2011;Krause B. et al, 2010;Walter J. et al, 2015c). Noteworthy, offline information from AUC, like for instance the optical properties of discrete QD fractions, could be implemented in evaluation routines based on UV/Vis spectroscopy.…”
Section: Analytical Ultracentrifugationmentioning
confidence: 99%
“…Analytical centrifugation as a direct and absolute technique, is a powerful technique for the characterisation of nanoparticles in colloidal systems [56]. For instance, Chiu et al showed that the results of LumiSizer were comparable with those obtained using dynamic light scattering, scanning electron microscope and zeta potential analysis [57].…”
Section: Stability Analysismentioning
confidence: 60%